Advanced counselling using training device and smartphone application on inhalation technique from metered‐dose inhaler with spacer equipped with different interfaces in asthmatic children. Issue 9 (4th June 2021) - Tony, Sara M.; Abdelrahman, Mona A.; Osama, Hasnaa; Abdelrahim, Mohamed E. A.
Abstract: Background: Spacers are equipped with either facemask or mouthpiece as an interface through which patient inhale their dose. The present study aimed to evaluate the effect of advanced counselling using training devices and smartphone applications on inhalation techniques from the metered‐dose inhaler (MDI) with a spacer equipped with different interfaces. Methods: 100 paediatric asthmatic children (8‐18 years) were divided into two groups. Group one was a spacer with a mouthpiece (n = 50) and group two was a spacer with a facemask group (n = 50). Both groups had three visits one month apart. At each visit, patients were asked to show the investigator their inhalation technique using MDI with spacer, and mistakes were recorded and then patients were trained on the proper inhalation technique of using MDI with a spacer. In the spacer with mouthpiece group, Flo‐Tone was attached to the mouthpiece to allow the Trainhaler smartphone application to detect the duration of inhalation. In the spacer with facemask group, there was no need to use the Flo‐Tone training device since the facemask was equipped with a built‐in whistle detected by the Trainhaler smartphone application. Results: The total number of mistakes in the inhalation technique decreased significantly ( P  < .05) in visits 2 and 3 for both groups. Duration of inhalation increased significantly ( P  < .05) in the mouthpiece group at visit 2 and in the facemask group at visit 3. Achieving 5 seconds of slow deep inhalation, breath‐holding for 5 seconds after inhalation and the tight fit of facemask represented the major obstacles in most children especially the youngest subjects. Breath out as far as comfortable had the highest number of mistakes in the first visit in both groups. Conclusion: The Flo‐Tone with its positive reinforcement whistle and the Trainhaler smartphone application significantly improved the inhalation technique by decreasing the total number of mistakes especially in important steps eg, shaking MDI, maintaining slow inhalation rate, breath‐holding after inhalation and appropriate facemask fitting. Also, they increased the duration of inhalation of asthmatic children from MDI with a spacer. Both spacer interfaces are easy to handle once taught well.